Augmenting communicative and collaborative skills in an ESP online group project - Mazura Jamalai@Jamali,; Pramela Krish, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Rapid technological advancements have resulted in a more user-friendly conducive virtual learning environment. Despite a vast corpus of research on online learning utilising an asynchronous online forum (OF) to improve English, studies on OF to improve English and develop 21st-century skills of communication and collaboration at the university level in Malaysia are still limited. This paper reports the use of OF via a learning management system (LMS) as a platform for teaching and learning in an English for Specific Purpose (ESP) course. This study comprised 26 participants from a public university to look at how OF was implemented in an ESP course to enhance communication and collaboration. Data from interviews and reflective journals were obtained from the participants during their involvement in OF. The findings of this study demonstrate that using OF helps students enhance their 21st century skills like communication and collaboration. It is evident that OF can become a recommended platform for enhancing students to improve 21st century skills based on the promising responses received from the participants in this study. The findings also suggest that OF is relevant for engagement of the language learners and may be worthy to be implemented in English courses or other courses tertiary level.